O processo de emancipação da escravidão no Brasil meridional (Alegrete, 1871-1911) - Sônego, Márcio Jesus Ferreira (2022)
This paper aims to analyze the process of emancipation and abolition of slavery in the municipality of Alegrete (western border of Rio Grande do Sul). The main issue we seek is to understand, through diverse historical sources, what the emancipationist and abolitionist proposals and initiatives were like, as well as the performance of the subjects involved and which sectors and segments participated in this process for the end of slavery in the municipality. Within this universe, we have verified that the antislavery movement was not restricted only to the actions of the political, economic and intellectual elite, but was also built by the actions of the enslaved and freed people themselves, who, through different possibilities and strategies, were protagonists in the overthrow of slavery. Thus, we seek to access the various fronts and forms of resistance developed by the captives in their search for freedom. In this way, our research analyzes and problematizes both the actions of emancipationists and abolitionists as well as the agency of the enslaved. As we advance in the post-abolition period (1888), tracing an overview of the attempts of insertion, conquests of rights, dynamics of sociability and experiences of freedmen and their descendants in the plan of work and daily life, we chose as a time frame the years from 1871 to 1911. The choice of this period is due to the fact that in 1871 the Lei do Ventre Livre (Free Womb Law) was approved, a law that regulated several situations regarding the issue of freedom for slaves in Brazil. The law represented a more incisive interference of the State in slave relations, also allowing slaves to access the provisions of this emancipation legislation in favor of their freedom. The final milestone of 1911 is due to the fact that it was the year of death of Onofre Nunes Quiroga, a former captive, in which we analyze some episodes of his trajectory, from slavery to freedom. In order to do so, we rely on the theoretical framework of the Social History of Slavery, Abolition, and Post-Abolition. The methodology of our study is influenced by Micro-History, mainly in the crossing of sources to reconstitute social trajectories and experiences, also based on the onomastic method, using the name as the conductor of the research. The main sources used were newspapers, letters of pardon, criminal processes, wills, post-mortem inventories, baptism, death and marriage registers, correspondence and reports from the City Council, parliamentary speeches, memorialistic reports, and the list of slave classification to be freed by the emancipation fund. The present study shows that, despite some similarities with the abolitionist movement developed nationally, such as the creation of emancipation and abolitionist clubs and associations, aimed at raising funds for the purchase of freedoms and also the use of the press as an important instrument in the fight against slavery, in Alegrete, the campaign had an emancipationist, moderate and gradual character in its activities, aiming at compensating the masters, through the granting of private freedoms, especially conditional. When the abolition was decreed, not all the freedmen and their descendants left the old properties, because, depending on the context and possibilities, they tried to reaffirm new working conditions and strategies for social mobility.